Theoretical description of the low-lying electronic states of LuBr located below 41, 700 cm−1. (March 2017) - Assaf, Joumana; Taher, Fadia; Magnier, Sylvie
Abstract: A theoretical investigation of the lowest molecular states of LuBr located below 41, 700 cm −1 in the 2S+1 Λ (+/−) and Ω (±) representations when including the spin-orbit effects, has been performed through SA-CASSCF and MRCI calculations. Potential energy curves have been determined for 21 2S+1 Λ (+/−) and 42 Ω (±) molecular states in the range of 1.70 to 3.50 Å and the spectroscopic constants (Re, Te, ωe and ωe χe ) have been deduced. Transition Dipole Moments have been computed for various allowed ΔΛ=0, ±1 on the same range of internuclear distances. In the case of the ground state and the two expected lowest singlet excited states (1) 1 Π and ( 2) 1 Σ +, a good agreement with the experimental results is obtained while new results are reported for the not yet observed 18 2S+1 Λ (+/−) and 42 Ω (±) states. A comparison with previous studies on the Lutetium mono-halides LuF, LuCl and LuI is presented, leading to trends in transition energies, equilibrium distances and dipole moments. Highlights: Quantum Chemistry calculations on the electronic structure of LuBr are presented. The spin-orbit coupling has been included. Potential energy curves and spectroscopic constants are presented for 21  2S+1 Λ (+/-) molecular states (without the spin-orbit coupling) and for 42 Ω (±) states (with the spin-orbit coupling).